The status of physical activity opportunities in Idaho schools. - Berei, Catherine P; Karp, Grace Goc; Kauffman, Katie (The Physical Educator, 2018)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-344-030-444-113 tex.type: [object Object]
Keywords: dept.hms

A PEP grant’s influence on change in a school district: One year post funding - Egan, Cate A.; Abel-Berei, Catherine P.; Karp, Grace Goc (Evaluation and program planning, 2021)
This study examined teachers' and administrators' perceptions of the institutionalization phase of the Carol M. White Physical Education for Progress (PEP) grant. A qualitative exploratory single case study (Yin, 2014) was utilized to examine the elements of the PEP grant that sustained or did not sustain after its conclusion, along with elements that were institutionalized and influences on this process. The findings were represented in the following three themes: (a) positive shifts, (b) backsliding, and (c) new directions, each with their own subthemes. Positive shifts includes sub-themes: (a) philosophy, (b) instruction, assessment and curriculum, (c) collaboration, and (d) respect. Backsliding includes sub-themes: (a) wellness team functioning, (b) the loss of PD and collaboration time, and (c) reduced data collection. New directions includes sub-themes: (a) mastery learning, (b) during school physical activity, (c) stress, and (d) administrative support. The factors that were institutionalized were quality physical education leadership roles, change in teachers' philosophies that influenced their instruction and assessment, and garnered administrative support. These elements were embedded into the physical education program and the school so much so that principals now expect the same type of programming from any new hire. Copyright © 2021 Elsevier Ltd. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: administration; administrative personnel; article; curriculum; dept.hms; funding; health education; human; human experiment; institutional framework; institutionalization; leadership; learning; peer-reviewed; perception; philosophy; physical activity; physical education; physiological stress; primary education; single-case study; student; teacher; teaching

Cultivating leadership, pedagogy and programming for CSPAP and healthy, active lifestyles at the University of Idaho. - Karp, Grace Goc; Brown, Helen; Scruggs, Philip W; Berei, Catherine P (The Journal of Physical Education, Recreation & Dance, 2017)
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-401-000-460-370 tex.type: [object Object]
Keywords: dept.hms

Perceptions of PEP grant influences on CSPAP implementation - Berei, Catherine P.; Karp, Grace Goc; Olsen, Simon; Fennell, Marcis; Drake, Elisa (Research Quarterly for Exercise and Sport, 2017)
tex.eissn: 2168-3824 tex.unique-id: ISI:000401115400154
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Stakeholders’ perspectives on the effects of a PEP grant on a district-wide CSPAP - Abel-Berei, Catherine P.; Karp, Grace Goc; Fennell, Marcis; Drake, Elisa M.; Olsen, Simon (Journal of Teaching in Physical Education, 2021)
A Comprehensive School Physical Activity Program (CSPAP) can help children be physically active for 60 min/day. Physical Education for Progress grants provided opportunities to improve physical education and physical activity programming. Purpose: This study explored stakeholders' perspectives on the effects of a Physical Education for Progress grant on a district-wide CSPAP. Method: Stakeholders included physical educators (n = 10; K-12), administrators (n = 6), and one superintendent. Individual, semistructured interviews were used to examine how the grant affected stakeholders' perspectives of the CSPAP. Results: The grant affected the CSPAP by providing (a) opportunities for professional development, (b) opportunities to establish a K-12 curriculum map, and (c) access to equipment and resources. Discussion: Framed in social ecological theory, intrapersonal, interpersonal, institutional, and community levels were influenced by the grant. Interactions between levels enabled changes in all CSPAP components, especially quality PE. Conclusion: A Physical Education for Progress grant is a successful mechanism to enhance a district-wide CSPAP. © 2021 Human Kinetics, Inc.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85099226945
Keywords: dept.hms; peer-reviewed

Guideposts and roadblocks to the career-long scholarly engagement of physical education teacher education faculty - Berei, Catherine P; Pratt, Erica; Parker, Melissa; Shephard, Kevin; Liang, Tanjian; Nampai, Udon; Neamphoka, Guntima (Research Quarterly for Exercise and Sport, 2017)
Purpose: Scholarship is essential for the growth and development of the physical education field. Over time, scholarship expectations have changed, forcing faculty members to alter time spent for research, teaching, and service. Social-cognitive career theory (SCCT) presents a model for understanding performance and persistence in an occupational environment. The interconnected aspects of SCCT have different emphasis related to self-efficacy, outcome expectations, or personal goals pursuit. This study explored physical education teacher education (PETE) faculty members' continuing engagement in scholarly activity through SCCT. Method: Data collection included interviews with 9 senior PETE faculty members who met the criteria for “productive scholars over time.” Curriculum vitae were collected to verify productivity. Results: Data analysis revealed guidepost themes that included collaborating, finding balance, defining a research process, and maintaining a strong work ethic. Roadblocks encountered included other obligations and lack of support for research. Conclusions: Participants demonstrated strong self-efficacy; held high, positive expectations for success; and set very specific, clear, and deliberate goals. Participant behavior was moderated by their personal attributes (capacity to build relationships, set goals, and maintain interest and passion) and was tempered by the environments in which they worked. Fostering similar behaviors has the potential to guide future and current PETE faculty members in creating supportive and encouraging atmospheres for sustained productivity. The lack of literature relating to this topic warrants the need for more research exploring the influential factors and benefits gained from sustained scholarly productivity over time for PETE faculty members.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-589-102-475-389 tex.type: [object Object]
Keywords: Academic publishing; Ethics; Professional; Female; Goals; Humans; Male; Physical Education and Training; Research; School Teachers; Self Efficacy; adult; atmosphere; barriers to productivity; career; curriculum; data analysis; dept.hms; expectation; faculty research productivity; female; higher education research; human; human experiment; interview; male; medical ethics; motivation; peer-reviewed; physical education; productivity; psychology; publishing; research; school teacher; self concept; teacher training; theoretical study